Coupling of mitochondrial function and skeletal muscle fiber type by a miR‐499/Fnip1/AMPK circuit. Issue 10 (9th August 2016) - Liu, Jing; Liang, Xijun; Zhou, Danxia; Lai, Ling; Xiao, Liwei; Liu, Lin; Fu, Tingting; Kong, Yan; Zhou, Qian; Vega, Rick B; Zhu, Min‐Sheng; Kelly, Daniel P; et al.
Abstract: Upon adaption of skeletal muscle to physiological and pathophysiological stimuli, muscle fiber type and mitochondrial function are coordinately regulated. Recent studies have identified pathways involved in control of contractile proteins of oxidative‐type fibers. However, the mechanism for coupling of mitochondrial function to the muscle contractile machinery during fiber type transition remains unknown. Here, we show that the expression of the genes encoding type I myosins, Myh7 / Myh7b and their intronic miR‐208b/miR‐499, parallels mitochondrial function during fiber type transitions. Using in vivo approaches in mice, we found that miR‐499 drives a PGC‐1α‐dependent mitochondrial oxidative metabolism program to match shifts in slow‐twitch muscle fiber composition. Mechanistically, miR‐499 directly targets Fnip1, an AMP‐activated protein kinase (AMPK)‐interacting protein that negatively regulates AMPK, a known activator of PGC‐1α. Inhibition of Fnip1 reactivated AMPK/PGC‐1α signaling and mitochondrial function in myocytes. Restoration of the expression of miR‐499 in the mdx mouse model of Duchenne muscular dystrophy (DMD) reduced the severity of DMD. Thus, we have identified a miR‐499/Fnip1/AMPK circuit that can serve as a mechanism to couple muscle fiber type and mitochondrial function. Synopsis: Muscle contractile machinery and energy production system must be precisely coordinated to maintain function, but the underlying mechanisms are unclear. This study reveals that miR‐499 in the myosin gene couples mitochondrial function to muscle fiber type and ameliorates muscular dystrophy in mdx mice. The expression of myosin contractile genes and their intronic miRNAs parallels mitochondrial function during muscle fiber type transition. miR‐499 embedded in the Myh7b gene drives an adaptive mitochondrial function to match shifts in muscle contractile machinery in mice. miR‐499 regulates mitochondrial function through direct inhibition of its target Fnip1, leading to activation of PGC‐1α, a well‐recognized transcriptional regulator of mitochondrial metabolism. The miR‐499 regulatory circuit is down‐regulated in the mdx mouse model of Duchenne muscular dystrophy (DMD) and restoring the expression of miR‐499 reduced the severity of DMD. Abstract : Muscle contractile machinery and energy production system must be precisely coordinated to maintain function, but the underlying mechanisms are unclear. This study reveals that miR‐499 in the myosin gene couples mitochondrial function to muscle fiber type and ameliorates muscular dystrophy in mdx mice.